Un legado inédito. Maria Antónia Leite Siza - Sequeira, M. (Arquitectura Viva, 2022)
Half a century after her early death, a book rescues the work of Maria Antónia Leite Siza: the catalogue of the exhibition on view till March 2023 at the Serralves Museum in Porto, presenting a hundred drawings recently donated to the institution by the artist’s husband, Álvaro Siza. Although curatorship usually involves a choice of what to include and exclude, Antónia Choupina – organizer of the show and editor of the publication – must have been convinced that given the overall quality and unpublished nature of the collection, the reasonable thing was not to make any selection or judgment, but to present all of it. The decision turned out correct because this striking graphic set of documents enriches our view of Portugal’s art scene of the 1960s and 1970s: a period in which geometric abstraction reigned supreme but with the figurative reemerging through Paula Rego’s first solo exhibition at the Modern Art Gallery of the Fine Arts School of Lisbon in 1966, and then through Maria Antónia Leite Siza’s first and only solo show at the Cooperative Árvore in Porto four years afterwards.